The role of Egypt's industrial policy in SMEs empowerment: A focus on industrial land allocation and licensing - Elkhishin, Dina (AUC Knowledge Fountain, 2017)
The objective of this thesis is to explore the relevance of the current industrial licensing and land allocation policy efforts to industrial SMEs needs in Egypt. The study analyzes the current situation of industrial licensing and land allocation frameworks and how they are facilitating the inclusion of SMEs in the industrial market. SMEs are core contributors to the Egyptian economy and hence assessing efforts undertaken to enhance their participation in the economy is of great importance. SMEs in Egypt, particularly in the industrial sector, are claimed to be not optimally performing as a result of longstanding structural and legislative and institutional barriers. The barriers chosen in this study are the access to land and industrial licensing barriers. The recent industrial policy implemented by the Ministry of Trade and Industry undertook specific legislative, institutional and operational reforms aiming at overcoming those barriers. Those reforms included changes in the investment law, enactment of a new industrial licensing law and amendments to laws governing the industrial land allocation system which resulted in widening the scope of mandates and responsibilities. The study applied qualitative research methods, particularly in-depth interviews with policy makers, industrial SMEs investors and policy experts. The analysis showed that recent policy efforts are promising, however, there are some challenges that might hinder the optimization of the outcomes of these polices. Ambiguity of some policy measures, overlapping reform measures and unclear implementation tools top the concluded challenges, whether for policy makers, policy implementers and/ or investors. For example, the differentiation between the role of IDA and GAFI in land allocation and industrial licensing is unclear. Also, coordination within the institutional authorities working on these policies reveals the continuation of a fragmented institutional framework in this regard. Further institutional, legal and operational reforms are still needed to optimize the outcomes of the new industrial policy in Egypt in favor of SMEs performance.